The Globalization of World Politics : An Introduction to International Relation - Baylis, John; Smith, Steve and Owens, Patricia (New York Oxford University Press, 2011)
Now in its fifth edition, this title has been fully revised and updated in the light of recent developments in world politics, with new chapters on the changing nature of war, human security, and international ethics.
Include Glossary, Reference and Index
Keywords: International relations -- World politics -- Globalization -- Globalization--Political aspects